2013
DOI: 10.1007/s10903-013-9789-5
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health of Foreign Domestic Workers: Exploring the Social Determinants

Abstract: Foreign domestic helpers constitute a significant proportion of migrant workers worldwide. This population subgroup provides an opportunity for understanding social determinants of oral health in immigrant community. A random sample of 122 Indonesian domestic helpers in Hong Kong completed a questionnaire on their demographic background, social characteristics (competency in local languages, immigration history, living condition, social connections, and leisure activities) and oral health behaviours (knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 10 publications
1
45
0
Order By: Relevance
“…Eighteen studies determined the effect of acculturation or its proxies on dental caries [4, 6, 20, 2931, 33, 38, 40, 41, 50, 53, 55, 61–65]. Among these studies, 5 reported that high acculturated immigrants and ethnic minorities had decreased number of teeth with dental caries [6, 20, 30, 62, 63] and 2 studies showed that low acculturation resulted in high rate of tooth decay [61, 64].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen studies determined the effect of acculturation or its proxies on dental caries [4, 6, 20, 2931, 33, 38, 40, 41, 50, 53, 55, 61–65]. Among these studies, 5 reported that high acculturated immigrants and ethnic minorities had decreased number of teeth with dental caries [6, 20, 30, 62, 63] and 2 studies showed that low acculturation resulted in high rate of tooth decay [61, 64].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, younger immigrants’ children and those who were born in the host country reported a lower level of dental caries than their counterparts [33, 41, 50, 55]. While host language proficiency was inversely associated with dental caries level in 3 studies [31, 40, 55], it was not significantly correlated with caries level in 2 other studies [29, 65].…”
Section: Resultsmentioning
confidence: 99%
“…All of the studies were published between 1975 and 2016 [21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81]. Twenty new studies were included in this update [26,27,28,29,31,38,39,40,44,45,…”
Section: Resultsmentioning
confidence: 99%
“…Twenty new studies were included in this update [26,27,28,29,31,38,39,40,44,45,47,49,50,53,59,61,66,67,79,81]. The language was predominantly English (96.7%).…”
Section: Resultsmentioning
confidence: 99%
“…This result has high policy relevance for local government to promote more social integration among internal migrants [ 21 ]. More incentives or promotions should be arranged for internal migrants to participate in these local social activities, such as community sports [ 58 ]. Moreover, for migrants with strong will to integrate, local government or communities should create the infrastructure or environment for them to bring their family members to town, so that their health could be improved with longer time of residence [ 59 ].…”
Section: Discussionmentioning
confidence: 99%